Human Liver Macrophage Subsets Defined by CD32 - Wu, Xia; Hollingshead, Nicole; Roberto, Jessica; Knupp, Allison; Kenerson, Heidi; Chen, Antony; Strickland, Ian; Horton, Helen; Yeung, Raymond; Soysa, Radika; Crispe, Ian N. (Frontiers in Immunology, 2020)
Human liver myeloid cells are imperfectly defined, but it is broadly agreed that cells of stellate appearance in situ, expressing the markers CD11b and CD68, are the liver’s resident macrophages, termed Kupffer cells. Recent investigations using single cell RNA sequencing and unsupervised clustering algorithms suggest there are two populations of cells with the characteristics of tissue macrophages in human liver. We therefore analyzed dissociated human liver tissue using the markers CD11b and CD68 to define Kupffer cells and found within this population two subsets that differ in their expression of multiple surface markers. These subsets were FACS-sorted based on CD32 expression, and gene expression analysis identified them with human liver myeloid cell subsets defined by two independent single cell RNA sequencing studies. These two subsets differed in the expression of genes associated with T cell activation and immunosuppression, suggesting distinct roles in T cell tolerance. In addition, one subset expressed two markers, CD1C and CD11c, more often seen on classical dendritic cells. Criteria used to distinguish macrophages from dendritic cells in other tissues may need to be revised in the human liver.